Improving nutrition budgeting in health sector plans: Evidence from India's anaemia control strategy - Avi Saini; Ritwik Shukla; William Joe; Avani Kapur (Wiley, 2022)
Abstract In India, 15 nutrition interventions are delivered and financed through the National Health Mission (NHM). Programmatic know‐how, however, on tracking nutrition budgets in health sector plans is limited. Following the four phases of the budget cycle-planning, allocations, disbursements and expenditure, this paper presents a new method developed by the authors to track nutrition budgets within health sector plans. Using the example of the Anemia Mukt Bharat (AMB) or Anemia Free India strategy, it reports preliminary findings on the application of the first two phases of the method, that is, to track and act for improved planning and allocations, covering 12 states. The paper lists out the budget heads, cost norms and developed tools to plan adequately. Supportive action was undertaken through sharing trends and trainings for AMB's budgeting to create opportunities for improvements. It was observed that the AMB budget increased over 3 years despite the COVID situation. It increased from INR 6184 million in FY 2019-2020 to INR 6293 million, a 2% increase in FY 2020-2021, and to INR 7433 million, an 18% increase in FY 2021-2022. The difference in allocations and planned budgets were low (16%, 4% and 11%, respectively) while the difference in required budgets and planned budgets were significant but reduced consistently (41%, 31% and 22%, respectively). The paper concludes that the methods adopted for tracking and acting for improved nutrition budgets helped in informing national and state governments regarding yearly trends. Such methods can be effective and be developed for other nutrition interventions.